Bispectral Index Can Reliably Detect Deep Sedation in Mechanically Ventilated Patients: A Prospective Multicenter Validation Study. (July 2017) - Wang, Zhu-Heng; Chen, Han; Yang, Yan-Lin; Shi, Zhong-Hua; Guo, Qing-Hua; Li, Yu-Wei; Sun, Li-Ping; Qiao, Wei; Zhou, Guan-Hua; Yu, Rong-Guo; Yin, Kai; He, Xuan; et al.
Abstract : BACKGROUND: Excessively deep sedation is prevalent in mechanically ventilated patients and often considered suboptimal. We hypothesized that the bispectral index (BIS), a quantified electroencephalogram instrument, would accurately detect deep levels of sedation. METHODS: We prospectively enrolled 90 critically ill mechanically ventilated patients who were receiving sedation. The BIS was monitored for 24 hours and compared with the Richmond Agitation Sedation Scale (RASS) evaluated every 4 hours. Deep sedation was defined as a RASS of −3 to −5. Threshold values of baseline BIS (the lowest value before RASS assessment) and stimulated BIS (the highest value after standardized assessment) for detecting deep sedation were determined in a training set (45 patients, 262 RASS assessments). Diagnostic accuracy was then analyzed in a validation set (45 patients, 264 RASS assessments). RESULTS: Deep sedation was only prescribed in 6 (6.7%) patients, but 76 patients (84.4%) had at least 1 episode of deep sedation. Thresholds for detecting deep sedation of 50 for baseline and 80 for stimulated BIS were identified, with respective areas under the receiver-operating characteristic curve of 0.771 (95% confidence interval, 0.714–0.828) and 0.805 (0.752–0.857). The sensitivity and specificity of baseline BIS were 94.0% and 66.5% and of stimulated BIS were 91.0% and 66.5%. When baseline and stimulated BIS were combined, the sensitivity, specificity, and clinical utility index were 85.0% (76.1%–91.1%), 85.9% (79.5%–90.7%), and 66.9% (57.8%–76.0%), respectively. CONCLUSIONS: Combining baseline and stimulated BIS may help detect deep sedation in mechanically ventilated patients. Abstract : Supplemental Digital Content is available in the text.Published ahead of print December 22, 2016.